Studi Teknoekonomi PLTS Apung 141,4 kWp Bendungan Telaga Tunjung Bali - Julius Mahendra Sihombing; Surung Rafael Sihaloho; I Nyoman Satya Kumara; I Wayan Sukerayasa; Wayan Gede Ariastina (Pusat riset dan Inovasi Nasional, 2025)
The increasing demand for electrical energy and the issue of climate change are driving the utilization of renewable energy, one of which is through Solar Power Plants (PLTS). The Province of Bali targets the development of PLTS of 108.2 MW, equivalent to 8.62% of the total solar energy potential of 1,254 MW by 2025. However, land limitations pose an obstacle to the construction of large-scale PLTS. Floating solar power plant design can be a solution to this issue. By utilizing 4,955.32 m² of water surface at the Telaga Tunjung Dam, the Floating Solar Power Plant at Telaga Tunjung Dam has a potential capacity of 141.4 kWp, using 280 Trina Solar modules of type TSM-DEG18MC.20(II) (505 Wp) combined with one SG110CX inverter with a capacity of 110 kW. The annual electricity production of the floating solar power plant, based on Helioscope software, is 201.1 MWh. The economic feasibility parameters used in this study include initial investment cost, Profitability Index (PI), and Payback Period (PP). The analysis results show that the 141.4 kWp floating solar power plant project at Telaga Tunjung Dam has an initial investment value of IDR 1,248,764,582, a PI of 1.26, and a PP of 3.91 years. Therefore, this project is considered economically feasible and contributes positively to reducing CO₂ emissions.